Mulheres na política: Myrthes Bevilácqua Corradi e Luzia Alves Toledo no poder legislativo - 1980 a 2018 - Lunz, Leandro da Silva (2019)
In this dissertation we analyze the political participation of Myrthes Bevilacqua Corradi in the National Congress and Luzia Alves Toledo the Senate and the Legislative Assembly of Espírito Santo, during the corresponding period from 1980 to 2018. With this research, we seek to reconstruct the political trajectory of these women and their contributions in a field of performance predominantly characterized by male power. At the same time, we intend to deconstruct the idea, during the period studied, that women would have the social role reserved for the private field, thus understanding the social identities built from the patriarchal point of view. Thus, we rescued the history of female participation in politics and investigated how their participation and performance represented the social interests of women, describing the circumstances that made it difficult for women to enter and perform in institutionalized politics in Brazil. main focus is the case of the State of Espírito Santo. The exercise of this rescue had as main methodological support the Oral History, through interviews and readings of the propositions. In this way, we articulate the analysis to contemporary debates on political participation, on the one hand, and on the history of women, feminism and gender relations, on the other.